Phenotypic, Biochemical, and Molecular Diversity Within a Local Emblematic Greek Allium sativum L. Variety - Anastasia Papadopoulou; Anastasia Boutsika; Francesco Reale; Silvia Carlin; Urska Vrhovsek; Eleftheria Deligiannidou; Aliki Xanthopoulou; Eirini Sarrou; Ioannis Ganopoulos; Ifigeneia Mellidou (Horticulturae)
Garlic, an asexually propagated crop, exhibits significant variation in its commercial traits and bioactive compounds. Despite its horticultural significance, the genetic pool available for breeding strategies is limited. This study aimed to assess the existing diversity within a popular garlic landrace from the region of “Nea Vissa”, Evros, Greece, focusing on phenotypic, biochemical, and molecular variation. In particular, bulb morphology, nutritional content, and organosulfur profiles were evaluated, along with genetic characterization using simple sequence repeat (SSR) markers to analyze intra-specific genetic variation. Our results revealed three distinct genetic clusters with moderate to low intra-varietal diversity. Morphological and biochemical characterization showed significant intra-specific diversity in both bulb morphology and nutritional content. Solid-phase microextraction (SPME) coupled with gas chromatography–mass spectrometry (GC–MS) analysis identified key volatile compounds, including allyl methyl disulfide and trisulfide, 1,2-dithiacyclopentene, cis-1-propenyl propyl disulfide, and cis-1-propenyl methyl disulfide in high abundances, suggesting that these were the predominant compounds characterizing the population. Our findings could be implemented to further enhance key phytonutrients in the local garlic population through breeding programs, targeting clones with high nutritional value and improved flavor and supporting germplasm conservation and utilization.